Prototipo recolector de agua atmosférica a partir de un sistema de Atrapanieblas en el sector Camellón Las Lajas-Tenjo, Cundinamarca, con punto de control en la vereda Los Colorados en el municipio de Pasca- Cundinamarca. (2021)
The purpose of this degree work is to present a new alternative for water collection, which has been implemented in various countries, and favorable results have been obtained in terms of water collection in places where there is a shortage of this resource, or where the household connection does not have the sufficient demand that a vulnerable population needs.